Understanding the wakeel’s roles of family Takaful as an intermediary at Takaful Ikhlas Sdn Bhd / Mohd Azman Pauzi - Pauzi, Mohd Azman (Faculty of Business and Management, 2011)
This project paper is prepared as a fulfilment of the Bachelor of Business Administration (Hons) Insurance. The topic for this study is “Understanding The Wakeel’s Roles of Family Takaful As An Intermediary at Takaful Ikhlas Sdn Bhd ”. Normally, people see an agent or wakeel as an intermediary for customer to purchase any family Takaful product as they didn’t know how to make the purchase. Customer or prospect think that any Takaful or insurance product must go through by the wakeel. The purpose of this study is to study the wakeel or agent service that they are truthly know they roles or just focus on the sales target . Not all of the customer really know of the product . In their mind, purchase the Takaful product is good enough to secure their future. It’s true but how far the product really meet customer need and want because every single person . have different financial strength, risk, demand etc. Mostly a good risk prospect is easily to have their protection but the problem is they didn’t know the whole contract and it become worse when the time of claim happen because the agent or wakeel not serve them well and miscommunication or lack of information and knowledge at the inception till the claiming process. From this study, researcher hope to help the people who seek or involve direct or indirectly of the Takaful should know that the wakeel roles is not limited to sell the product but extend to guide and consult from the starting point untill all the ending process, helping the customer to make thing efficience and effective. To make that happen, firts the prospect that have intention to buy Takaful product need to know the wakeel roles and know customer’s right in every scope the need to know. Chapter one consist of the background of the Takaful Ikhlas Sdn Bhd, concept of Takaful business and meaning of islamic term they use.Chapter two consist of literature review, chapter three research methodology and desing, chapter four consist data analysis and interpretation of data and lastly chapter five is conclusion and recomendation that relevant to this research.